Alcohol‐induced miR‐155 and HDAC11 inhibit negative regulators of the TLR4 pathway and lead to increased LPS responsiveness of Kupffer cells in alcoholic liver disease. Issue 2 (5th June 2017) - Bala, Shashi; Csak, Timea; Kodys, Karen; Catalano, Donna; Ambade, Aditya; Furi, Istvan; Lowe, Patrick; Cho, Yeonhee; Iracheta‐Vellve, Arvin; Szabo, Gyongyi
Abstract : Alcohol downregulates IRAK‐M, SHIP1, SOCS1, and IL‐10, inhibitors of TLR4 signaling, via NF‐κB‐induced miR‐155 and HDAC11 in Kupffer cells. Abstract : Inflammation promotes the progression of alcoholic liver disease. Alcohol sensitizes KCs to gut‐derived endotoxin (LPS); however, signaling pathways that perpetuate inflammation in alcoholic liver disease are only partially understood. We found that chronic alcohol feeding in mice induced miR‐155, an inflammatory miRNA in isolated KCs. We hypothesized that miR‐155 might increase the responsiveness of KCs to LPS via targeting the negative regulators of LPS signaling. Our results revealed that KCs that were isolated from alcohol‐fed mice showed a decrease in IRAK‐M, SHIP1, and PU.1, and an increase in TNF‐α levels. This was specific to KCs, as no significant differences were observed in these genes in hepatocytes. We found a causal effect of miR‐155 deficiency on LPS responsiveness, as KCs that were isolated from miR‐155 KO mice showed a greater induction of IRAK‐M, SHIP1, and suppressor of cytokine signaling 1 after LPS treatment. C/EBPβ, a validated miR‐155 target, stimulates IL‐10 transcription. We found a higher induction of C/EBPβ and IL‐10 in KCs that were isolated from miR‐155 KO mice after LPS treatment. Gain‐ and loss‐of‐function studies affirmed that alcohol‐induced miR‐155 directly regulates IRAK‐M, SHIP1, suppressor of cytokine signaling 1, and C/EBPβ, as miR‐155 inhibition increased and miR‐155 overexpression decreased these genes in LPS or alcohol‐pretreated wild‐type KCs. HDAC11, a regulator of IL‐10, was significantly increased and IL‐10 was decreased in KCs that were isolated from alcohol‐fed mice. Functionally, knockdown of HDAC11 with small interfering RNA resulted in an IL‐10 increase in LPS or alcohol‐pretreated Mϕ. We found that acetaldehyde and NF‐κB pathways regulate HDAC11 levels. Collectively, our results indicate that the alcohol‐induced responsiveness of KCs to LPS, in part, is governed by miR‐155 and HDAC11.